Building bridges to emotion: Developing a standardized film-based emotion elicitation tool for Iranian culture - Milad Yousefi; Jamal Amani Rad (PLoS ONE, 2026)
Emotion elicitation through culturally relevant stimuli is crucial for psychological research that seeks to explore affective processes within specific populations. This study aimed to develop and validate a film-based emotion elicitation tool for Iranian culture. A comprehensive database of short video clips was selected to evoke distinct emotional states, including happiness, tenderness, fear, anger, sadness, and disgust, alongside neutral clips as controls. To validate the database, the emotional responses of 300 Iranian participants were assessed using key dimensions of arousal and valence, positive and negative affective states, gender differences, and mixed emotions. The results indicated that all emotional stimuli elicited significantly higher arousal levels compared to neutral clips, with fear-inducing clips generating the highest arousal levels. In terms of valence, positive emotional films, such as those inducing happiness and tenderness, were significantly associated with higher pleasantness, while anger elicited the lowest valence scores, indicating its strong negative impact. Additionally, the video clips effectively differentiated between positive and negative affective states, with clear statistical significance observed across all comparisons ( p < 0.0001 ), showing that videos designed to evoke positive emotions (e.g., happiness) and negative emotions (e.g., fear) successfully achieved these outcomes across the participant group. Gender differences were also examined, with women generally showing higher levels of emotional arousal than men, particularly in response to happiness, tenderness, sadness, and disgust, though the overall effect sizes were small. Finally, the study delved into the complexity of mixed emotions, where participants often experienced simultaneous conflicting emotions, such as happiness and sadness, challenging traditional discrete emotion frameworks. The findings affirm the cultural relevance and efficacy of the developed video clip database in eliciting a wide range of emotional responses, making it a valuable tool for future psychological studies in Iranian contexts. This study underscores the importance of culturally specific stimuli in emotion research and provides a robust resource for exploring the emotional landscape within Iranian culture.